Supplementary data for Carbon dioxide dynamics in an agricultural headwater stream driven by hydrology and primary production. (Wallin et al. DOI: 10.5194/bg-2019-486) - Wallin, Marcus (Uppsala University, 2020)
Hourly measured CO2 concentration data from a 11.3 km² temperate agricultural stream, collected over more than one year (a total of 339 days, excluding periods with ice and snow cover).

The dataset was originally published in DiVA and moved to SND in 2024.

Hourly measured CO2 concentration data from a 11.3 km² temperate agricultural stream, collected over more than one year (a total of 339 days, excluding periods with ice and snow cover).

Datasetet har ursprungligen publicerats i DiVA och flyttades över till SND 2024.
Supplementary data for Carbon dioxide dynamics in an agricultural headwater stream driven by hydrology and primary production. (Wallin et al. DOI: 10.5194/bg-2019-486)
Keywords: ATMOSPHERIC CARBON DIOXIDE; HEADWATER STREAM; AGRICULTURAL LANDS; WATER TEMPERATURE; dynamics; dynamik; agricultural streams; agricultural streams; hotspots for emission; hotspots for emission; Environmental Sciences; Miljövetenskap